Assessing the current state of quality improvement training in urology in the UK: Findings from the General Medical Council 2018 trainee survey. (March 2021) - Pallari, Elena; Hughes-Hallett, Archie; Vitoratou, Silia; Khadjesari, Zarnie; Cornford, Phil; Morley, Roland; Sevdalis, Nick; Green, James S. A.
Objective: The General Medical Council (GMC) of the UK has identified the need to support doctors through education in safety and quality improvement (QI) methods. This study reports findings from the GMC annual survey of 2018 from urology trainees regarding the state of QI training and their training needs. Material and methods: We designed a set of four questions to assess how QI methods are being taught nationally, and inserted them in the 2018 annual GMC trainee survey for urology. This is a cross-sectional study assessing the current state of QI training and mentoring received by trainees, and their self-assessed ability and confidence in completing a QI project as part of training requirements. Data were statistically analysed in Stata 15 stratified by Local Education Training Boards (LETBs)/Deanery and by specialty trainee level (ST3–7). Results: In total, 270 responses were received from urology trainees. Data showed significant variation across the country. Responses from ST3–7 trainees ranged from 5–20% on completing more than three QI projects, while 7–58% replied that they had done none. Across all ST grades, 40% of trainees stated they had not undertaken QI, whereas 0–27% reported they had not received any mentoring on QI to date. There was significant variation across training regions too: 11–74% of trainees answered that they have received training in QI methods, and 58–100% responded that they were confident in undertaking QI projects. Across all LETBs, 1–3% responded that they uploaded projects on national websites for dissemination; finally, a range of 0–18% stated they had completed more than three projects. Conclusion: This is the first national snapshot of QI training for the entire urology specialty in the UK. The study demonstrates wide variation in QI training and activity undertaken by trainees, and shows a lack of systematic implementation of QI education across training regions. Level of evidence: 2c